(3JOhjf GdSfI GdfHhjI (B:s (3fTCJg hJWhQg ef GdbQf GdChd Edj fgGjI GdbQf GdJGSY GdgLQj (B/s - (3GdRgQGfj, eMeO Hf eWQ s 1368 (3gLQj(B-s ((3GdQjGV (B- (3GdeedcI GdYQHjI GdSYhOjI (B:s (3ecJHI OGQ GdefgGL ddfTQ hGdJhRjY ,s, 2007)
(3GdcJGH OQGSI LGeYI CcGOjejI JYQV cja HOC JOhjf CMGOjK GdSfI GdfHhjI hcja JWnqhQ YHQ GdYUhQ GdESdGejI GdeNJdaI, ef GdbQf GdChd GdgLQj Edi GdbQf GdJGSY, eY GdJQcjR Ydi eQGMd GdJOhjf, ef GdfGMjI GdRefjI hGdefgLjI(B.s
Keywords: (3GdMOjKs -- (3LeY hJOhjfs -- (3JGQjN GdMOjKs